The Role of Progesterone in Elf5 Activation and Milk Component Synthesis for Cell-Cultured Milk Production in MAC-T Cells - Hyuk Cheol Kwon; Hyun Su Jung; Do Hyun Kim; Jong Hyeon Han; Sung Gu Han (Animals, 2024)
Prolactin is essential for mammary gland development and lactation. Progesterone also induces ductal branching and alveolar formation via initial secretory differentiation within the mammary gland. Herein, we aimed to evaluate the role of progesterone as a prolactin substitute for the production of cell-cultured milk components in MAC-T cells. Cells were treated with various hormones such as prolactin (PRL), progesterone (P4), 17β-estradiol (E2), cortisol (COR), and insulin (INS) for 5 d. MAC-T cells cultured in a P4 differentiation media (2500 ng/mL of P4, 25 ng/mL of E2, 25 ng/mL of COR, and 25 ng/mL of INS) showed similar levels of E74-like factor 5 (Elf5) and milk component synthesis (α-casein, β-casein, α-lactalbumin, β-lactoglobulin, and triglycerides) compared to those cultured in a PRL differentiation media (5000 ng/mL of PRL, 500 ng/mL of CORT, and 50 ng/mL of INS). The levels of α-casein and triglycerides in the optimal P4 differentiation media were present at comparable levels to those in the PRL differentiation media. Our results demonstrated that P4 induces the activation of Elf5 and the synthesis of milk components in MAC-T cells, similar to PRL. Therefore, P4 may be used as an effective substitute of PRL for cell-cultured milk production in in vitro frameworks.